Tendency in tip polarity changes in non-contact atomic force microscopy imaging on a fluorite surface - Kyeyune, Bob; Rahe, Philipp; Reichling, Michael (Beilstein Journal of Nanotechnology, 2025)
We investigate the impact of tip changes on atomic-scale non-contact atomic force microscopy (NC-AFM) contrast formation when imaging a CaF2(111) surface. A change of the atomic contrast is explained by a polarity change of the tip-terminating cluster or by a polarity-preserving tip change via the re-arrangement of the foremost atoms. Based on the established understanding of the unique contrast patterns on CaF2(111), polarity-preserving and polarity-changing tip changes can be identified unambiguously. From analyzing a large set of images, we find that the vast majority of tip changes tend to result in negative tip termination. This analysis delivers hints for tip configurations suitable for stable imaging of CaF2(111) surfaces.
Keywords: atomic resolution imaging; calcium fluoride surface; interaction force; non-contact atomic force microscopy (NC-AFM); tip change